Supercell [videorecording (DVD)] - Ulrich, Skeet; Heche, Anne; Diemer, Daniel; Baldwin, Alec, 1958- (Saban Films, 2023)
Baseball-size hail, violent winds, and churning tornadoes make supercells deadly, and when William Brody was a boy, his father a legendary storm-chaser was killed by one. Now, the family business belongs to Zane Rogers, a reckless tour operator who sees dollar signs where others see storm clouds. When his destiny arrives in the form of one of the most powerful storms on record, William leaves his mom and home behind to team up with his father's ex-partner, Roy Cameron, barely surviving a tornado yet determined to chase on nature's most terrifying creations: the bear's cage.